Constructive approach for synthesis of a functional IgG using a reconstituted cell-free protein synthesis system - Murakami, Satoshi; Matsumoto, Rena; Kanamori, Takashi (Scientific reports, 2019)
IgG is an indispensable biological experimental tool as well as a widely-used therapeutic protein. However, cell culture-based expression of monoclonal IgG is costly and time-consuming, making this process difficult to use for high-throughput screening in early-stage evaluation of biologics. With the goal of establishing a fast, simple, and robust high-throughput expression system for IgG, we implemented the synthesis of functional aglycosylated IgG by constructive approach based on a reconstituted prokaryotic cell-free protein synthesis system (PURE system). Optimization of the PURE system revealed that the following factors and reaction conditions were needed for IgG synthesis: (1) inclusion of the disulfide bond isomerase DsbC, (2) adjustment of the GSH/GSSG ratio, (3) inclusion of the molecular chaperone DnaK and its cofactors, and (4) use of an extended incubation time. Synthesis temperature and template DNA ratio (light chain-/heavy chain-encoding) also had been optimized for each IgG. Under optimal conditions, peak production of the anti-HER2 antibody trastuzumab reached 124 µg/mL. Furthermore, the active forms of other IgGs, including IgG1, IgG2, and IgG4 subclasses, also were synthesized. These results provide basic information for the development of novel high-throughput expression and functional screening systems for IgG, as well as useful information for understanding the IgG synthesis process.